From solar building design to Net Zero Energy Buildings: performance insights of an office building - Aelenei, Laura Elena (2014)
Net Zero-Energy Buildings Performance has gained more attention since the publication in 2010 of the EPBD recast [1]. Successful implementation of such an ambitious target depends on a great variety of factors. With a literature full of theoretical advice and a building industry rife with myths about the value of technologies, the present study intend to unveil an sustainable framework for sharing insights into NetZEB methodology applied in an Portuguese office building, Solar XXI, based on the authors experience in the ongoing research carried out within International Energy Agency SHC Task 40 - ECBCS Annex 52, "Towards Net Zero Energy Solar Buildings”.